Meeting the nutritional needs of seniors via a seafood rich diet - McManus, Alexandra; Hunt, Wendy; Creegan, Rhona (Curtin University, 2015)
Research has shown a gap in the market for information around the types of protein rich, bioavailable meals that would be suitable for seniors who are capable of, and have the facilities to prepare their own meals at home. Seniors can experience significantly more nutritional risk factors associated with chronic lifestyle conditions than the general population. Inadequate nutritional intake in older people is common, frequently overlooked, and results in many negative health outcomes including malnutrition. This study was a mixed methods, quasi experimental trial involving both qualitative and quantitative data collection methods. The main aim of the study was to develop a series of low cost, nutritionally balanced meals specifically designed to meet the needs of seniors.